Analysis of the Performance of Blue Chip Stock of Cigarette Companies Listed on the Indonesia Stock Exchange - Yulis Nurul Aini (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This study aims to: 1. Understand how the performance of the cigarette industry in the Indonesia Capital Market. 2. Understand the best performance in the cigarette industry. The research data was obtained from secondary data published on the Indonesia Stock Exchange and information company website in the form of financial reports for the period 2018-2020. The financial statement is analyzed using profitability ratios to explain the performance of each cigarette industry. The Profitability ratio used is ROE, ROA, and NPM. The data analysis method is descriptive and comparative by comparing the results of the calculation of the profitability ratios with the industry average standard. The result of this study indicates that the performance of the cigarette industry was very good in PT. Hanjaya Mandala Sampoerna Tbk.